AGE-FRIENDLY INITIATIVES AND REDUCING SOCIAL ISOLATION: ROLES OF PHYSICAL ENVIRONMENT AND COMMUNITY ENGAGEMENT. (16th November 2018) - Cao, K; Dabelko-Schoeny, H; Choi, M; White, K
Abstract: Social isolation affects the physical and mental health of elders. Although previous literature identified risk factors for social isolation (e.g. living alone, unmarried, and social participation), few studies examined the impact of the physical environment. Informed by the theory of social determinants of health, this study examines the effects of participating in community/social events and the physical environment on an indicator of elders' health, namely the perceived disconnectedness from their community, employing the binomial hierarchical logistic regression. The sample consists of elders aged 50 and older (n=342) living in a large metropolitan Midwest city who participated in a community needs assessment survey for the World Health Organization's Global Network of Age-Friendly Cities and Communities initiative. Results indicate that elders without access to ramps to enter buildings are 4.76 times as likely to perceive disconnectedness as those with the access. Those answering "not sure" to access to well-maintained public buildings are 4.39 times as likely to perceive disconnectedness as those without the access, implying that unawareness of access may increase isolation. Those who identify transportation as a barrier are 6.77 times as likely to perceive isolation as those who do not. Additionally, a reduction in participation of social/community events is associated with an increased likelihood of perceived disconnectedness (Adjusted Odds Ratio 1.75). The current study underscores the importance of improving access to public buildings, ramps, and transportation to reduce the perceived disconnectedness of elders. Future studies should continue exploring effects of age-friendly initiatives on social isolation and social determinants of health.